Uganda : The Sexually Transmitted Infections Project - Mulusa, Mary (World Bank, Washington, DC, 2012)
There is evidence suggesting a change in the HIV incidence in Uganda, where its prevalence has dropped in certain communities, and age groups, most notably among women in the 15-29 years age group. The note reviews key features of the Sexually Transmitted Infections Project in the country, identifying change in sexual behavior as the most important approach to preventing HIV spread. The Project also emphasized on mitigation of the personal impact of AIDS, supporting treatment, training of health workers, and provision of drugs, in addition to institutional development, gender issues, and global partnerships. But regardless, of the high level of general awareness of HIV/AIDS, the positive trends observed do not mean that the epidemic has been overcome in Uganda, where current prevalence levels still present an enormous challenge. Lessons address political commitment, and local ownership as essential to overcome the epidemic, highlighting the work of the Namungalwe Women Task Force, whose activities, partly contributed to mitigating the epidemic. Nonetheless, there is the need to mobilize resources to support HIV/AIDS programs, and to use multi-sectoral interventions to deal with the epidemic, as well as capacity building in technical, and management skills, and, information for monitoring programs in a sustainable manner.